2011
DOI: 10.1089/sur.2009.028
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Enforcement of Ventilator-Associated Pneumonia Prevention Strategies in Trauma Patients

Abstract: There was a statistically significant decrease in the occurrence of VAP with strict enforcement of a VAPP protocol, regardless of head AIS score. Although the difference in patients with a head AIS score <3 was not statistically significant, it was clinically meaningful, decreasing the already-low rate of VAP by half. Strict enforcement of VAPP protocols may be cost efficient for hospitals and prevent decreased reimbursement under the Medicare pay-for-performance strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…11-14,22 While a causal inference remains elusive, these bundles are likely effective, because they provide a clear and manageable set of expectations in a complex health care environment. Bundles help providers translate evidence into practice by summarizing and simplifying the strongest evidence, and providing reminders to adhere to evidence-based practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11-14,22 While a causal inference remains elusive, these bundles are likely effective, because they provide a clear and manageable set of expectations in a complex health care environment. Bundles help providers translate evidence into practice by summarizing and simplifying the strongest evidence, and providing reminders to adhere to evidence-based practices.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a 7-item VAP prevention protocol decreased VAP in trauma patients, but the origins of this protocol are not described. 14 In contrast, the development of a European VAP prevention bundle that uses multi-criteria decision analysis (MCDA) is described in detail; 4 however, this bundle may not reflect the perceptions of US providers.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, controversial issues of practice aimed at reducing nosocomial infection like the timing of tracheostomy, trans-pyloric feeding, stress ulcer prophylaxis, and early extubation take on a new importance. (32, 33) Most studies have concluded that early vs. late tracheostomy in the setting of severe TBI does not change mortality, however, there is converging evidence showing that early tracheostomy decreases ventilation days (34) and evidence-based protocols for early extubation can decrease incidence of pneumonia. (32, 33) We cannot comment widely, however, on the mechanism that may underlie the long-term effect of HAP.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies provided data on program infrastructure costs, and 1 study estimated reductions in total costs for patients requiring long-term mechanical ventilation and reductions in direct cost per case. 15,16 Strategies to Improve Adherence…”
Section: Resultsmentioning
confidence: 99%